The Use of ICT: The Mediating Role of Attitudinal Beliefs, Subjective Norms, Behavioral Control and Behavioral Intentions among Saudi Elementary Teachers - Almarri, Jaber; Rashid, Rabiatul Adawiah Ahmad (Journal of Posthumanism, 2025)
The present investigation explored behaviours towards Information and Communication Technology (ICT) among 239 primary teachers (59.4% male, 40.6% female) in Dammam, Saudi Arabia. A convenience sampling technique was used to choose the sample. Based on the Decomposed Theory of Planned Behaviour (DTPB) model, the study addressed a research gap investigating technology adoption in a centralised education system. The analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM) and the mediating effects of attitudes on the path between perceived ease of use towards ICT (β = 0.131, p = 0.003) and perceived usefulness of ICT (β = 0.386, p < 0.001) and behavioural intention towards ICT was statistically significant. Subjective norms mediated peer (β = 0.128, p < 0.001) and superior (β = 0.070, p = 0.001) influences on behavioural intention; however, student influence was not significant, contrary to a similar Western investigation. The results indicate that behavioural intention significantly predicts actual use (β = 0.305, p < 0.001). Contrary to DTPB theory, the results indicate that perceived behavioural control did not mediate any relationships. The model explained 26.1% of the variance in ICT use (R² = 0.261), lower than that identified in a related Western investigation. A notable distinction with differences identified in explanatory power (R²) and predictive relevance (Q²) indicated some theoretical constraints. The findings highlighted the compatibility assumptions associated with technology adoption in a centralised education system. The recommendations highlighted the importance of modifying teachers' attitudes and developing peer networks, rather than providing resources, to increase technology use within the Saudi educational system. Keywords: ICT usage, attitudinal beliefs, subjective norms, perceived behavioural control, the DTPB model, Saudi primary education.